2022
DOI: 10.3389/fdgth.2022.828686
|View full text |Cite
|
Sign up to set email alerts
|

The Developments and Iterations of a Mobile Technology-Based Fall Risk Health Application

Abstract: Falls are a prevalent and serious health concern across clinical populations. A critical step in falls prevention is identifying modifiable risk factors, but due to time constraints and equipment costs, fall risk screening is rarely performed. Mobile technology offers an innovative approach to provide personalized fall risk screening for clinical populations. To inform future development, this manuscript discusses the development and testing of mobile health fall risk applications for three unique clinical pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous research has emphasized the importance of user-centered design 1 processes in developing effective mHealth apps for various health domains, such as self-management of chronic conditions ( 21 , 22 ), mental health ( 23 ), persons living with HIV ( 24 , 25 ), women in substance use recovery ( 26 ), and participants with fall risk ( 27 ). Schnall et al ( 24 ) conducted formative research, which included focus groups, participatory design sessions, and usability evaluations, to guide the development of a health management app for individuals living with HIV.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has emphasized the importance of user-centered design 1 processes in developing effective mHealth apps for various health domains, such as self-management of chronic conditions ( 21 , 22 ), mental health ( 23 ), persons living with HIV ( 24 , 25 ), women in substance use recovery ( 26 ), and participants with fall risk ( 27 ). Schnall et al ( 24 ) conducted formative research, which included focus groups, participatory design sessions, and usability evaluations, to guide the development of a health management app for individuals living with HIV.…”
Section: Related Workmentioning
confidence: 99%
“…Through an iterative design process, the authors showed that users’ feedback helped tailor an mHealth app to maximize usability, access, and safety for this at-risk population. Lastly, Hsieh et al ( 27 ) aimed to provide personalized fall risk screening for clinical populations, including older adults, individuals with Multiple Sclerosis, and wheeled-device users, by utilizing mHealth apps. The authors developed the interface of each app with a user-centered design approach through iterative usability testing and semi-structured interviews.…”
Section: Related Workmentioning
confidence: 99%